Nepalese Medical Students in the COVID-19 Pandemic: Ways Forward - Guragai, Mandeep (JNMA J Nepal Med Assoc, 2020)
The coronavirus disease 2019 has not hit Nepal as hard as it has the rest of the world (as of 4th April 2020). Countries are reporting a saturation in healthcare facilities and facing a rise in demand for human resources for health. It is difficult to predict the extent of the disease transmission in Nepal in the absence of epidemiologic and statistical analysis in our context. But based on calculations made by epidemiologists in other countries, there seems to be a significant possibility of an outbreak in our communities too. Medical students can be a valuable human resource in a variety of ways to aid in the country's response to a possible outbreak. However, their involvement in the pandemic comes with its own challenges. Thorough planning and preparation must be done before allowing medical students to take part in the battle against the pandemic.